From the movie Disney Pixar Inside out : the essential guide - Bynghall, Steve (London : DK Pub., 2015)
"Delve inside Riley's mind and explore the amazing world of Disney-Pixar's 'Inside Out.' Meet Joy, Sadness, Fear, Anger, and Disgust-- the Emotions whose tricky job it is to keep Riley safe and happy. Discover Headquarters, explore the Subconscious, and get to know Riley's imaginary friend Bing Bong in this adventure-packed guide"--Page 4 of cover.
3-6.
Keywords: Inside out (Motion picture) -- Juvenile literature; Emotions in motion pictures -- Juvenile literature; Mood (Psychology) -- Fiction